USING THE CAPABILITIES OF DIGITAL TECHNOLOGIES IN MAKING INVESTMENT DECISIONS - Musabekov Ulugbek Jorobekovich (Journals Park Publishing, 2023)
This article discusses the financial, organizational, technical and innovative components of the strategy of investing in digital technologies. The work is of practical importance because it combines approaches to financial and technological support of investment activities with the development of in-depth information and computer technologies. The elements of the model are proposed from the point of view of introducing components of the digital environment, making managerial decisions in the investment process, expanding the role of the banking sector in investment processes, the introduction of new SupTech and RegTech tools will be. Development of consulting services at various stages of investment project implementation from preparation of business plans, preparation of feasibility studies and investment memoranda to evaluation of real results of project implementation.